Knowing on trust - Faulkner, Paul, 1969- (Oxford : Oxford University Press, 2011)
Paul Faulkner presents a new theory of testimony - the basis of much of what we know. He addresses the questions of what makes it reasonable to accept a piece of testimony, and what warrants belief formed on that basis. He rejects rival theories and argues that testimonial knowledge and testimonially warranted belief are based on trust.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Knowledge, Theory of